Influence of lupin-based milk alternative heat treatment and exopolysaccharide-producing lactic acid bacteria on the physical characteristics of lupin-based yogurt alternatives. (June 2016) - Hickisch, A.; Beer, R.; Vogel, R.F.; Toelstede, S.
Abstract: In the present study we investigated the influence of heat treatment of lupin-based (LB) milk alternatives and different exopolysaccharide (EPS)-producing lactic acid bacteria on the physical characteristics of set-type LB yogurt alternatives. LB milk alternatives, obtained from protein isolate of Lupinus angustifolius cv. Boregine, were either pasteurized at 80 °C for 60 s or ultra-high temperature (UHT) heated at 140 °C for 10 s and was fermented with Lactobacillus plantarum TMW 1.460 and 1.1468, Pediococcus pentosaceus BGT B34 and Lactobacillus brevis BGT L150. Fermentation duration was strongly affected by heat treatment: different strains needed between 25 to 35 h in UHT LB milk alternative to reach a pH of 4.5 compared to 14 to 24 h in pasteurized LB milk alternative. EPS extraction revealed slightly higher amounts of EPS for UHT LB yogurt alternatives ( 0.5–0.9 g/l; pasteurized: 0.4–0.7 g/l). The more intensive heat treatment (UHT) resulted also in better rheological (apparent viscosity, hysteresis loop area, flow point, elastic, viscous and complex modulus) and textural properties (firmness, consistency, cohesiveness and index of viscosity) of the investigated LB yogurt alternatives. Furthermore, LB yogurt alternatives out of UHT milk alternative revealed a lower tendency to syneresis, measured with siphon and centrifugation method. This work contributes to the fundamental knowledge of the textural properties of LB yogurt alternatives. Graphical abstract: Highlights: Ultra-high temperature (UHT) treatment of lupin-based (LB) milk alternatives improved physical properties of respective yogurts compared to pasteurization. Fermentation duration was longer in UHT than in pasteurized LB milk alternative. Microorganisms produced more exopolysaccharides in UHT than in pasteurized LB milk alternative.